Government by Code? Blockchain Applications to Public Sector Governance - Bustamante, Pedro; Cai, Meina; Gomez, Marcela; Harris, Colin; Krishnamurthy, Prashant; Law, Wilson; Madison, Michael J.; Murtazashvili, Ilia; Murtazashvili, Jennifer Brick; Mylovanov, Tymofiy; Shapoval, Nataliia; Vee, Annette; et al. (Frontiers in Blockchain, 2022)
Studies of blockchain governance can be divided into analysis of governance of blockchains (such as rules and power dynamics within a given network) and governance by blockchains (such as how blockchains can be implemented to improve self-governance of community-based peer production networks). Less emphasis has been placed on applications of distributed ledgers to public sector governance. Our review clarifies that the decentralization and distributive features enable blockchains to link up loosely connected private organizations and public agencies, as well as improve efficiency and transparency of government transactions. However, most blockchain applications lack clear advantages over conventional digital recording of information. In addition, our review highlights that blockchain applications in public sector governance are potentially vast, though in most instances, the existing applications have not extended much beyond limited-scale pilots. We conclude with a call for construction of indexes of public sector implementations of blockchains, as none yet exist, as well as for additional research to understand why blockchains have not been more widely deployed by governments.